A study exploring knowledge, attitudes and behaviours towards autism among adults applying to a Family Health Center in Istanbul - KARAVUŞ, MELDA (KARE PUBL, 2016)
OBJECTIVE: The aim of this study was to assess knowledge, awareness, behavior and attitudes towards autism among applicants to a Family Health Center (FHC). METHODS: This descriptive study was performed at a Family Health Center (FHC) in Istanbul in August 2013. Data was obtained via face-to-face interviews with participants older than 18 years who were admitted to the FHC. The questionnaire consisted of questions on sociodemographic characteristics, applicants' knowledge of autism and their approach to autism. RESULTS: 160 applicants participated in our survey of which 38.8% had heard the word 'autism' Knowledge and awareness of autism, and attitudes and behaviours towards this disorder differed significantly with the educational level of the study participants (p<0.05) However, these parameters did not change with gender and income level of the participants (p>0.05). CONCLUSION: The most important outcome of our study is that awareness, or even having knowledge of the word autism is significant in breaking down stereotypes. Despite the low level of awareness of the disease, the majority of the participitants had a positive attitude towards autism.
Keywords: Autism; awareness; education; knowledge